(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
Recognition of Prior Learning (RPL) is a key strategy for validating skills acquired through non-formal learning by formal assessment. In India, RPL has been positioned as important milestone under the Skill India Mission to enhance employability, social inclusion, lifelong learning and certification by recognising the skill earned by the vocational workers. However, despite a strong policy framework, the implementation of RPL faces persistent challenges such as low awareness, limited worker preparedness, assessment anxiety, certification and career progression. This article argues that these challenges are largely developmental rather than procedural and can be minimized through structured frame work interventions. The present study conducted among the vocational workers in the construction sectors by using structured questionnaire. The major objective focused for the research is does the sample respondents are interested in getting formal certification for their learned skill through non formal and how they perceive the present career.